Book Review: Marius Telea, Istoria și spiritualitatea Imperiului Bizantin (The History and Spirituality of The Byzantine Empire), vol. I: Istoria Imperiul Imperiului Bizantin (The History of The Byzantine Empire), Alba Iulia, Editura Reîntregirea, 2021, 884 p. - DUȘE, Călin Ioan (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2022)
Associate Professor Marius Telea’s work The History and Spirituality of The Byzantine Empire (Istoria și spiritualitatea Imperiului Byzantine), volume I: The History of The Byzantine Empire (Istoria Imperial Imperiului Byzantine), deals with the most critical aspects of the Byzantine Empire from its founding in 330 until its fall on May 29, 1453. This work, essential for knowing the history of the great Byzantine Empire, is structured in eighteen chapters, from page 29 to page 724, and each chapter has rich bibliography in foreign languages and Romanian. At the end of the book, the author presents six appendices, which allow the reader to quickly capture the most critical events in the history of the Byzantine Empire.